Ketamine Blocks Morphine-Induced Conditioned Place Preference and Anxiety-Like Behaviors in Mice - McKendrick, Greer; Garrett, Hannah; Jones, Holly E.; McDevitt, Dillon S.; Sharma, Sonakshi; Silberman, Yuval; Graziane, Nicholas M. (Frontiers in Behavioral Neuroscience, 2020)
Patients suffering from opioid use disorder often relapse during periods of abstinence, which is posited to be caused by negative affective states that drive motivated behaviors. Here, we explored whether conditioning mice with morphine in a CPP training paradigm evoked anxiety-like behavior during morphine abstinence. To do this, mice were conditioned with morphine (10 mg/kg, i.p.) for five days. 24 h following conditioning, anxiety levels were tested by measuring time in the open arms of the elevated plus maze. The next day, mice were placed in the three compartment chamber to measure morphine-induced conditioned place preference (CPP). Our results show that following morphine conditioning, mice spent significantly less time in the open arm of the elevated plus maze and expressed robust morphine CPP on CPP test day. Furthermore, we found that an acute treatment with (R,S)-ketamine (10 mg/kg, i.p.), a medication demonstrating promise for preventing anxiety-related phenotypes, 30 min. prior to testing on post conditioning day 1, increased time spent in the open arm of the elevated plus maze in saline- and morphine-conditioned mice. Additionally, we found that a second injection of ketamine 30 min. prior to CPP tests on post conditioning day 2 prevented morphine-induced CPP, which lasted for up to 28 d post conditioning. Furthermore, we found that conditioning mice with 10% (w/v) sucrose using an oral self-administration procedure did not evoke anxiety-like behavior, but elicited robust CPP, which was attenuated by ketamine treatment 30 min. prior to CPP tests. Overall, our results suggest that the ketamine-induced block of morphine CPP may not be attributed solely to alleviating negative affective states, but potentially through impaired memory of morphine-context associations.